Acidente com material biológico na equipe de Enfermagem da regional de Araraquara: caracterização das exposições ocupacionais com abandono ao tratamento - Damiani, Matilde (Universidade Federal de São Carlos, 2020)
According to the definition of the Ministry of Health, accidents at work with exposure to biological material, is a case of occurrence with any occupational category, with direct or indirect exposure of the worker to organic material potentially contaminated by pathogens (viruses, bacteria, fungi, prions, and protozoa) through material perforating or not. Such accidents, in general, affect health professionals in the exercise of their work activities, including all those who in their working process are exposed, directly or indirectly, to biological fluids. This situation is exacerbated when health workers, especially nursing professionals, who are the focus of this work, live with manifestations of dissatisfaction, illness, and lack of health protection measures, which makes them vulnerable to exercise their functions. Thus, the aim of this study is to raise and analyze work accidents with biological material reported to CEREST, in the period between 2013 and 2017, occurring in health establishments in the nursing team, with a record of abandonment, as well as identify conducts at the time of the accident and thus scale the applicability of constitutional rights against the risks to which those professionals are exposed. The results show that the municipality of Araraquara presents 50% of the 131 notifications of treatment abandonment, with the nursing technician being the most affected professional. Women represent 82.44% of these workers aged 19 to 29, the age when they are entering the job market and starting a family. Chemoprophylaxis was indicated for 15% of the victims, without additional information on the evolution of the case. The data show that treatment abandonment is frequent, with insufficient information in the Health Information System. Thus, it is urgent that CEREST Araraquara and the health managers of the municipalities of coverage, implement educational actions to prevent accidents and improve the quality of this information at SINAN.
Accident with biological material in the Nursing team of the region of Araraquara: categorization of occupational exposures with abandonment to treatment
Keywords: Acidente de trabalho; Material biológico; Enfermagem; CEREST; Sistema de Informação de Agravos; Work accident; Biological material; Nursing; Health Information System; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA